PENGUKURAN KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN ANALISIS DISKRIMINAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rijajami, Wassito (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
Financial performance is an analysis used to see how far the company has implemented good and healthy financial regulations. To determine the condition of good and healthy financial performance is to use financial ratio analysis, financial ratio analysis is an activity to analyze financial reports to assess financial performance based on a certain period. This study aims to describe the financial performance, liquidity ratios, solvency ratios, profitability ratios and activity ratios as well as to measure the company's financial performance in terms of liquidity ratios, to measure the company's financial performance from solvency ratios, to measure the company's financial performance from profitability ratios and to measure company's financial performance from activity ratios as well as to measure the company's financial performance using discriminant analysis. Data analysis was performed using discriminant analysis techniques using the Altman Z-Score method. In this study, the data collection technique was using documentation techniques, the documentation was carried out by collecting all secondary data obtained from the official website of the Indonesian Stock Exchange (IDX). The results of the research show that there are 18 companies that have good or healthy financial performance and there is 1 company whose financial performance is in the grey area.